2016
DOI: 10.5037/jomr.2016.7101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Head and Tongue Posture on the Pharyngeal Airway Dimensions and Morphology in Three-Dimensional Imaging: a Systematic Review

Abstract: ObjectivesNatural head position is recommended to be optimal at cone-beam computed tomography acquisition. For standardization purposes in control of treatment outcome, it is clinically relevant to discuss, if a change of posture from natural head position may have an effect on the pharyngeal airway dimensions and morphology, during computed tomography, cone-beam computed tomography or magnetic resonance imaging acquisition. This was the aim of the present literature review study for purposes of valid evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 53 publications
0
54
0
1
Order By: Relevance
“…The inconsistency of these results is probably due to the differences in the CBCT protocols used between studies where head posture, tongue position and segmentation procedures were not heterogeneous. Furthermore, the control of the position of the tongue and the soft palate are still factors that can influence the three‐dimensional evaluation of the pharyngeal airways …”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency of these results is probably due to the differences in the CBCT protocols used between studies where head posture, tongue position and segmentation procedures were not heterogeneous. Furthermore, the control of the position of the tongue and the soft palate are still factors that can influence the three‐dimensional evaluation of the pharyngeal airways …”
Section: Discussionmentioning
confidence: 99%
“…craniofacial morphology and head posture) and focusing the attention on the effects of treatment interventions on the skeletal basis that may influence airway patency. 5,6,16,17 Nevertheless, some of the issues mentioned in these studies remain not completely answered due to the presence of technical drawbacks that hinder the reduction of the systematic errors. In the present study we presented a technical analysis able to overcome these limitations with the aim to characterize three-dimensionally the upper airway by using as references only stable, reproducible anatomical landmarks, which will not be affected by orthognathic surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, head posture and tongue position during CBCT-acquisition has also been advocated to be an important factor for UA morphology, yet often underestimated as reported in a previous systematic review. 16 Regarding the second issue ("standard reference planes"), it has to be underlined that, the selection of reliable landmarks for upper airway analysis is of the outmost importance, even more when the changes are the result of orthognathic surgery. A variety of anatomic landmarks have been proposed, however, some refer to anatomical structures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review conducted by Gurani et al (28) both airway volume and CSA showed an increase when evaluated in respect to head extension, head rotation, altered body position, and jaw protrusion. Therefore, the radiographic technique was standardized during CBCT scan in this study.…”
Section: Discussionmentioning
confidence: 99%